2020
DOI: 10.1002/pc.25860
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanical and thermomechanical properties of flax/glass fiber hybrid‐reinforced epoxy composites

Abstract: A hybrid fiber‐reinforced plastic (HFRP) composite is defined as a composite material that is reinforced by two or more continuous fiber materials in the same resin matrix. This article used the hand layup method to prepare epoxy‐based flax and glass HFRP composites. Under the same fiber hybrid ratio, the interlayer and sandwich hybrid lamination methods were used for mechanical properties testing of the composite. The tensile and bending properties of the HFRP composites were obtained by tensile and three‐poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…The sound absorption coefficient of the composites was tested in the frequency range 63 to 6300 Hz, and the maximum sound absorption coefficient was observed for the hybrid composites. The increased mechanical properties and sound absorption coefficient suggest the potential application of the epoxy hybrid composites containing glass/sisal and tea powder in automobiles components, soundproofing materials, and interior paneling Wang et al [76] studied the effect of hybridizing flax fiber sheets with glass fiber sheets in epoxy composites. Different combinations of hybrid composites with eight layers were fabricated, and among the composites prepared, G2F4G2 (two glass fiber sheets each sandwiched over four layers of flax) showed very high FS and FM compared to neat flax fiber-reinforced epoxy composites.…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…The sound absorption coefficient of the composites was tested in the frequency range 63 to 6300 Hz, and the maximum sound absorption coefficient was observed for the hybrid composites. The increased mechanical properties and sound absorption coefficient suggest the potential application of the epoxy hybrid composites containing glass/sisal and tea powder in automobiles components, soundproofing materials, and interior paneling Wang et al [76] studied the effect of hybridizing flax fiber sheets with glass fiber sheets in epoxy composites. Different combinations of hybrid composites with eight layers were fabricated, and among the composites prepared, G2F4G2 (two glass fiber sheets each sandwiched over four layers of flax) showed very high FS and FM compared to neat flax fiber-reinforced epoxy composites.…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…Furthermore, the flexural properties of the hybrid composites were significantly higher than the various studied composites; i.e., 40 wt.% chopped GF reinforced in BA-a/EPN copolymer [ 42 ], 20 wt.% Kevlar Fiber reinforced in poly(BA-a) [ 43 ], and flax/basalt fibre laminates with epoxy resin [ 44 ]. However, the flexural strength and modulus were significantly lower than the flax/GF hybrid epoxy composites [ 17 ]. This can be attributed to the usage of the flax fiber mats in earlier investigations, whereas the laminates in the current study were made using micro SDPF fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been reported on the mechanical and thermomechanical properties of hybrid composites made with bio-based and synthetic fibers. Wang and coworkers evaluated the flax/GF sandwich structured hybrid composites made with epoxy resin [ 17 ]. They stipulated that the flax fibers as core and GF at the outer surface formation have the best thermomechanical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the optimum value, bonding the fiber with the matrix becomes difficult, likely due to agglomerations, and that results in a weak interface between the fiber and the epoxy matrix leading to poor mechanical properties [ 123 ]. The fiber’s orientation and layer-stacking sequence can affect the tensile properties, for example, natural fibers and glass layers bound to one another have more tensile properties than changing layers stacking sequences, and a hybrid composite with fibers aligned along the load has the best tensile properties [ 100 , 102 , 108 ]. The glass bonding fiber layers were shown to have higher tensile properties than fiber bonding glass layers [ 114 ].…”
Section: Mechanical Properties Of Epoxy-based Natural Fiber Biocompos...mentioning
confidence: 99%